You are on page 1of 7

Techniques of Integration Draft 1

Felix Guo, Russell Kim


December 2015

Integration by Substitution

If the integral is made up of two terms, one of which is a derivative of another, then
(Integration by Substitution) can be used. For example:
Z
sin(x) cos(x) dx
letu = sin(x)
du = cos(x)dx
Z

1
1
u du = u2 du = sin2 (x)
2
2

This can also be used in the case of


tor.

x
x2

as the derivative of the denominator is the numera-

Integration by Parts

The general formula is defined as:


Z

Z
u dv = uv

2.1

v du

x sin(x)
Z
x sin(x) dx
u=x
du = dx

dv = sin(x) dx
v = cos(x)
1

Z
x sin(x) dx =

u dv
Z
= uv v du
Z
= xcos(x)

cos(x)dx

= xcos(x) + sin(x) + C

2.2

Natural Log
Z
ln(x)dx
u = ln(x)
dv = dx
1
v=x
du = dx
x
Z
Z
ln(x)dx = u dv
Z
= uv v du
Z
1
= ln(x) x x dx
x
= ln(x) x x + C

2.3

Doing it Twice
Z

u = t2
du = 2t dt
Z

t2 et dt
dv = et dx
v = et

2 t

t e dt =

u dv
Z
= uv v du
Z
2 t
= t e 2 et t dt
dv = et dx
v = et

u=t
du = dt
2

2 t

t e 2

2 t

e t dt = t e 2(uv
= t2 et 2(tet

v du)
Z

et dt)

= t2 et 2(tet et ) + C
= t2 et 2tet + 2et + C

2.4

Reduction Formula
Z

sinn (x)dx

u = sinn1 (x)
du = (n 1)sinn2 (x)cos(x) dx
Z

sin (x) = cos(x)sin

n1

Z
(x) + (n 1)

Knowing that cos2 (x) = 1 sin2 (x)


Z
Z
n
n1
sin (x) = cos(x)sin (x) + (n 1)
Z
n1
= cos(x)sin (x) + (n 1)(
Z
n1
= cos(x)sin (x) + (n 1)
Z
Z
n
n1
n sin (x) = cos(x)sin (x) + (n 1)
Z
Z
n1
1
n1
n
sin (x) = cos(x)sin (x) +
n
n

dv = sin(x)dx
v = cos(x)
sinn2 (x)cos2 (x) dx

sinn2 (x)(1 sin2 (x)) dx


Z
n2
sin (x) dx sinn2 (x)sin2 (x) dx)
Z
n2
sin (x) dx (n 1) sinn (x) dx)
sinn2 (x) dx
sinn2 (x) dx

Integration of Trigonometric by Substitution

By using substitution, we can solve some integrals that are more complex, for example odd
numbered integrals. However, we need to ensure that the integrand has both sin(x) and
d
cos(x) terms (because of dx
sin(x) = cos(x).)
If we wanted to find:

cos3 (x) dx

Wed need to know the identity sin2 (x) + cos2 (x) = 1 and cos2 (x) = 1 sin2 (x)

Replacing the equation:


Z

cos (x) dx =
Z
=

cos(x)cos2 (x) dx
cos(x)(1 sin2 (x)) dx

u = sin(x)
Z

du = cos(x) dx

cos(x)(1 sin2 (x)) dx =

(1 u2 ) du

1
= u u3 + C
3
1
= sin(x) sin3 (x) + C
3
If there is an odd power of sin or cos, we can seperate it to convert the remaining even power
and substitute. However, if there are only even powers, we need to use half angle identities
such as:
1
sin2 (x) = (1 cos(2x))
2

1
cos2 (x) = (1 + cos(2x))
2

1
sin(x)cos(x) = sin(2x)
2

Tangent and secant can also be used in this way.


If the power of secant is even, save a factor of sec2 (x) and use sec2 (x) = 1 + tan2 (x) to
express the remaining factors in terms of tan(x) with the substitution u = tan(x).
If the power of tangent is odd, save a factor of sec(x)tan(x) and use tan2 (x) = sec2 (x) 1
to express the remaining factors in terms of sec(x) with the substitution u = sec(x).
Also note that:
Z
tan(x) dx = ln|sec(x)| + C
Z
sec(x) dx = ln|sec(x) + tan(x)| + C

3.1

Trigs with Multiples of X

To evaluate the integrals

sin(mx)cos(nx) dx or other variations:

1
sin(A)cos(B) = [sin(A B) + sin(A + B)]
2
1
sin(A)sin(B) = [cos(A B) cos(A + B)]
2
1
cos(A)cos(B) = [cos(A B) + cos(A + B)]
2
4

Trigonometric Substitution

R
Trignometric substitution is primarily used when encoutering the form
a2 x2 where
Pythagoras can be used and applied to a right angle triangle. This technique works because
we substitute x = asin() thus:
p
p
p

a2 x2 = a2 a2 sin2 () = a2 (1 sin2 ()) = a2 cos2 () = a|cos()|


Here are general trigonometric substitutions:
Expression

Substitution

Identity

a2 b 2 x 2

x = ab sin()

1 sin2 () = cos2 ()

a2 + b 2 x 2

x = ab tan()

1 + tan2 () = sec2 ()

b 2 x 2 a2

x = ab sec()

tan2 () = sec2 () 1

Ex. 1
Z
9 x2
dx
x2
Let x = 3 sin(). Then dx = 3 cos() d and
p
p

9 x2 = 9 9 sin2 () = 9 cos2 () = 3|cos()| = 3cos()


Z
Z
9 x2
3 cos()
dx =
3 cos() d
2
x
9 sin2 ()
Z
cos2 ()
=
d
sin2 ()
Z
= cot2 () d
Z
= (csc2 () 1) d
= cot() + C
Ex. 7
Z

x
dx
3 2x x2

We must first complete the square in the denominator, where:


3 2x x2 = 3 (x2 + 2x) = 3 + 1 (x2 + 2x + 1) = 4 (x + 1)2
5

This suggests that we make the substitution u = x + 1. Then du = dx and x = u 1.


Z
Z
x
u1

dx =
du
3 2x x2
4 u2

We can substitute u = 2 sin(), giving du = 2 cos() d and 4 u2 = 2 cos(), so


Z
Z
2 sin() 1
x

dx =
2 cos() d
2 cos()
3 2x x2
Z
= (2 sin() 1) d
= 2 cos() + C
 

1 u
2
+C
= 4 u sin
2 


x+1
1
2
= 3 2x x sin
+C
2

Substitution with Partial Fractions

Substitution with partial fraction is used as a strategy for integrands in the form of:
Z
P (x)
where deg(P (x)) < deg(Q(x))
Q(x)
Factor the denominator as completely as possible and find the partial fraction. For each
factor in the denominator we get term(s) in the decomposition according to the following
table.
Ex.

Z
Solution I:

7x2 + 13x
dx
(x 1)(x2 + 4)

4
3x2
16
+
+ 2
dx
x1 x+4 x +4
3
x
= 4 ln|x 1| + ln(x2 + 4) + 8 tan 1( )
2
2
Z

Solution II:
7x2 + 13x
A
Bx + C
=
+ 2
2
(x 1)(x + 4)
x1
x +4
=

A(x2 + 4) + (Bx + C)(x 1)


(x 1)(x2 + 4)

Set numerators equal and equate like terms.


7x2 + 13x = (A + B)x2 + (C B)x + 4A C
Set coefficients equal to get a system and solve to get constants.
C B = 13
B=3

A+B =7
A=4

4A C = 0
C = 16

Formulas
d
dx

d
dx

1
1x2

csc1 (x) = xx12 1

d
dx

d
dx

sin1 (x) =

sinh1 (x) =

1
1+x2

csch1 (x) = |x|1x2 +1

d
dx

1
cos1 (x) = 1x
2

d
dx

sec1 (x) =

d
dx

cosh1 (x) =

d
dx

1
x x2 1

1
x2 1

1
sech1 (x) = x1x
2

d
dx

tan1 (x) =

1
1+x2

d
dx

1
cot1 (x) = 1+x
2

d
dx

tanh1 (x) =

d
dx

1
1x2

1
coth1 (x) = 1x
2

Z
tan(u) du = ln|sec(u)| + C

cot(u) du = ln|sin(u)| + C

Z
sec(u) du = ln|sec(u) + tan(u)| + C

csc(u) du = ln|csc(u) cot(u)| + C